Staff Guidance Note for Public Debt Sustainability Analysis in Market-Access Countries. (Policy Papers; Policy Paper ;, 2013)
The framework for fiscal policy and public debt sustainability analysis (DSA) in market-access countries (MACs) was reviewed by the Executive Board in August 2011.1 The review responded to shortcomings in identifying fiscal vulnerabilities and assessing risks to debt sustainability against the backdrop of increased concerns over fiscal policy and public debt sustainability in many advanced economies.